Threading on - Lee, Jia Wen (2019)
Threading On is a feature writing package that explores the eyebrow threading industry in an increasingly image-conscious Singapore. Our project explores a range of topics, which includes the flourishing eyebrow threading industry, the origin of threading, the recent trend of men going for threading, alternative eyebrow grooming methods and the challenges faced by businesses in the industry. The newsmakers are owners of threading salons, threaders, and their customers. We also spoke to people outside of the threading scene – image consultants, professors, market experts, and more – to help us better understand the trends and inner workings of the industry.